2007
DOI: 10.2320/matertrans.48.722
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Atomic Structures of Boron Nitride Nanotubes with Cup-Stacked and Fe Nanowire Encapsulated Structures

Abstract: Boron nitride (BN) nanotubes, nanohorns, nanocoils were synthesized by annealing Fe 4 N and B powders at 1000 C in nitrogen gas atmosphere. Especially, Fe-filled BN nanotubes, bamboo-type and cup-stacked type BN nanotubes were produced. Formation mechanism and nanostructures were investigated by high-resolution electron microscopy, high-angle annular dark-field scanning transmission electron microscopy, electron diffraction, energy dispersive X-ray spectroscopy and molecular mechanics calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Furthermore, since the properties of low-dimensional materials strongly depend on their structural characteristics (such as size, shape, and surface states), the controllable synthesis of one-dimensional (1D) BN nanostructures is extremely important with regard to investigations of their fundamental properties [15]. So far, few reports have focused on the growth mechanism of BN nanomaterials (usually considering only one special synthesis condition), and very rarely has there been a comprehensive study on the effect of growth conditions on the structure and formation mechanism of these nanostructures [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, since the properties of low-dimensional materials strongly depend on their structural characteristics (such as size, shape, and surface states), the controllable synthesis of one-dimensional (1D) BN nanostructures is extremely important with regard to investigations of their fundamental properties [15]. So far, few reports have focused on the growth mechanism of BN nanomaterials (usually considering only one special synthesis condition), and very rarely has there been a comprehensive study on the effect of growth conditions on the structure and formation mechanism of these nanostructures [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 20(a) shows TEM image of BN nanotubes with a cup-stacked structure after purification process (Oku et al 2007). Diameters and lengths of the BN nanotubes are in the range of 40-100 nm and 5-10 μm, respectively.…”
Section: Bn Nanotubes With Cup-stacked Structuresmentioning
confidence: 99%
“…They showed that Ni-BNNTs are promising low-temperature catalysts for CO oxidation. The encapsulation of various metal nanostructures inside CNTs and BNNTs has been successfully demonstrated by different groups using experiments and molecular dynamics simulations (see, for example, [20,[23][24][25][26]), but very few works in this field have used conventional applied mathematical modelling. Mathematical modelling, together with efforts of experimentalists and molecular dynamics (MD) simulations, can provide a deeper understanding of the interactions between molecules.…”
Section: Introductionmentioning
confidence: 99%